2006
DOI: 10.1002/adma.200501277
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Low‐Field Magnetoresistance in Sr2Fe2–xMoxO6–δ by Oxygen Cycling and the Role of Excess Mo (x > 1) in Grain‐Boundary Regions

Abstract: Oxygen cycling of Sr2Fe2–xMoxO6–δ (SFMO) samples allows the resistivity and low‐field magnetoresistance (LFMR) to be precisely cycled. TEM shows that the change in resistivity with oxygen is not only a consequence of the change in oxygen stoichiometry of SFMO, but also a concomitant change in the Fe/Mo ratio in SFMO. The figure shows the change in MR and resistivity (values in mΩ cm above the data points for samples D1–D7) with increasing post‐annealing time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…The presence of an insulator located at grain boundaries rises the tunneling barrier, increasing thus the magnetoresistance. Such an insulator role can be played by small amounts of SrMoO 4 impurity [17,34,41,43,45,51,52] or by oxygen incorporated at grain boundaries [13]. These effects (difficultly separable one from the others) indicate that highest magnetoresistance is obtained for samples having small grains and low antisite disorder.…”
Section: Magnetoresistancementioning
confidence: 99%
“…The presence of an insulator located at grain boundaries rises the tunneling barrier, increasing thus the magnetoresistance. Such an insulator role can be played by small amounts of SrMoO 4 impurity [17,34,41,43,45,51,52] or by oxygen incorporated at grain boundaries [13]. These effects (difficultly separable one from the others) indicate that highest magnetoresistance is obtained for samples having small grains and low antisite disorder.…”
Section: Magnetoresistancementioning
confidence: 99%
“…This behavior arises from the half-metallic character of Sr 2 FeMoO 6 , in which a spin-polarized band of Mo t 2g -O 2p-Fe e g states crosses the Fermi level [16]. The magnetoresistive behavior has also been shown to be impacted by the presence of insulting grain-boundaries (when low magnetic fields are applied) and, because of this low-field magnetoresistance, Sr 2 FeMoO 6 has been investigated for use in spintronic devices [23,29,30]. To better understand the origins of the aforementioned properties, and to better utilize these properties in technological applications, it is necessary to know what oxidation states are adopted by Fe and Mo in these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Redox issues have to be also considered as Mo is in a 6+ oxydation state in SMO while is 5+ in SFMO. Sharma et al 17 have determined the phase stability of SFMO as a function of oxygen partial pressure P O 2 in a H 2 /CO 2 atmosphere and MacManus-Driscoll et al 18 observed molybdenum enrichment in the SFMO grain boundary when studying the effect of cyclic oxygenation on low-field magnetoresistance.…”
Section: Introductionmentioning
confidence: 99%